(untitled) (Ameghiniana, 2013)
A new record of flamingos of the Familia Phoenicopteridae (Charadriiformes), proceeding from the El Morterito Formation (Upper Tertiary), Valle del Cajón, Catamarca Province, Argentina, is described. The characteristics of the material indicate a relationship with fossil and extant species of the genus Phoenicopterus, as well as similarities with Presbyornis from the Lower Eocene of Patagonia (Argentina) and Palaelodus from the Upper Oligocene-Lower Miocene of France.